2018
DOI: 10.1038/s41598-018-23119-6
|View full text |Cite
|
Sign up to set email alerts
|

Random networks of core-shell-like Cu-Cu2O/CuO nanowires as surface plasmon resonance-enhanced sensors

Abstract: The rapid oxide formation on pristine unprotected copper surfaces limits the direct application of Cu nanomaterials in electronics and sensor assemblies with physical contacts. However, it is not clear whether the growing cuprous (Cu2O) and cupric oxides (CuO) and the formation of core-shell-like Cu-Cu2O/CuO nanowires would cause any compromise for non-contact optical measurements, where light absorption and subsequent charge oscillation and separation take place such as those in surface plasmon-assisted and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…In addition to bare Cu films, we considered Cu films with surface oxide since the surface of nanosized Cu films is susceptible to oxidation and surface oxidation reduces film conductivity 26 . The Cu films get oxidised easily not only when it is in contact with air but also during its growth in a ultra-high vacuum chamber 27,28 . Figure 2b shows the presence of copper oxide (Cu-O) on the surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to bare Cu films, we considered Cu films with surface oxide since the surface of nanosized Cu films is susceptible to oxidation and surface oxidation reduces film conductivity 26 . The Cu films get oxidised easily not only when it is in contact with air but also during its growth in a ultra-high vacuum chamber 27,28 . Figure 2b shows the presence of copper oxide (Cu-O) on the surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Cu nanowires were synthesized by a hydrothermal route, [30], [31], [33] whereas their Pd and Pt modified derivatives were obtained by galvanic replacement reactions [34] similar to those as we reported earlier.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have shown that Cu nanowires are suitable for SERS, in particular, when dispersed on Au thin films [30]. Although rapid oxidation of common metals may influence the local field and thus spectral amplification, in the case of Cu, the native surface oxides [31] do not seem to degrade SERS quality [30], [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Core-shell nanowires with a metal core and dual-oxide shells comprising native oxides are the only ones that have been successfully synthesized, e.g., Cu/Cu 2 O/CuO or Cu/Cu 2 O/ZnO [ 9 , 10 ]. Our group successfully synthesized template-free and surfactant-free Ag nanowires with a uniform spontaneous ultra-thin titania shell (~0.5 nm) on TiO 2 coated Si substrate [ 11 ].…”
Section: Introductionmentioning
confidence: 99%